(untitled) (Research, Society and Development, 2021)
Parasitic diseases are considered neglected diseases, with high occurrence in Brazil. Public squares are important leisure areas frequented by children, youth, adults and the elderly, however, such areas have a large number of animals, which eliminate feces in these places, increasing the transmission of zoonotic parasitic diseases. This study aimed to determine the occurrence of parasites in public squares soils in the municipality of Patos, Paraíba state, Brazilian semiarid region. Five samples of 100 g of sand banks were collected from 28 public squares from November 2018 to April 2019, totaling 140 samples. Processing was done using the simple sedimentation method. Of the 28 squares in 27 (96.43%) parasites were found in the soil, and of the 140 soil samples in 74 (52.85%) some type of parasitic agente was found, all identified as helminths. In the 28 squares, the absolute and relative frequencies were 25 (89.2%) for Ancylostoma spp., 13 (46.4%) for Strongyloides spp., eight (28.6%) for Trichuris spp., seven (25% ) for Enterobius vermicularis and six (21.4%) for Toxocara spp. (P < 0.0001). Of the total number of samples (n = 140), 50 (35.7%) were positive for Ancylostoma spp., 18 (12.9%) for Strongyloides spp., nine (6.4%) for Trichuris spp., seven (5%) for Enterobius vermicularis and six (4.2%) for Toxocara spp. (P < 0.0001). Of the 140 samples, 74 (52.85%) presented some parasitic form, 60 (81%) had only one type of parasitic species and 14 (19%) were polyparasitic. There was a greater density of positivity in the central area of ​​the city. In this way, better planning is suggested in the maintenance of these spaces with a view to guaranteeing environmental health and, consequently, promoting animal and human health.